PERANCANGAN CINEMA CENTER DI JEMBRANA - NI LUH NARITI; IDA BAGUS IDEDHYANA; SILUH PUTU NATHA PRIMADEWI (Universitas Mahasaraswati K. Mataram, 2024)
Cinema Center namely the building which is the center of film activities. In January 2023 Indonesia has 500 cinema units with an increase in the number of viewers by 15.4% from year to year previously. However, the distribution of screens is still considered uneven, because it is not affordable reaching small towns in every existing district/city, including on the island of Bali. Jembrana became strategic location for building construction cinema new, apart from due to public interest strong towards film, Jembrana also does not have entertainment facilities such as cinemas. The purpose of This research includes feasibility studies, design specifications, basic concepts and design themes. This research uses a qualitative descriptive approach with data collection methods in the form of observation and literature. Data processing in the form of data reduction, data presentation, drawing conclusions, synthesis and transformation methods. The design results for the Cinema Center in Jembrana refer to the concept a recreational and educational basis with an architectural theme, namely Green Architecture to support environment. This facility was built on a land area of 10,838.24 m² in Jl. Udayana no. 1, Baluk, Jembrana with space requirements of 13,005.88 m². The design of the cinema center in Jembrana takes into account the design concepts that have been prepared, including the site design concept, building design concept, structure and materials concept and utility concept